Statistics in psychology : an historical perspective - Cowles, Michael, 1940- (L. Erlbaum Associates, 2001)
Topics addressed in this second edition include: the development of statistics; science, psychology and statistics; the organization of data probability; sampling and estimation; comparisons, correlations and predictions; the design of experiments; the rise of ANOVA; and the statistical hotpot.